Plankton Dataset During Austral Spring and Summer in the Valdés Biosphere Reserve, Patagonia, Argentina - Ariadna Celina Nocera; Maité Latorre; Valeria Carina D’Agostino; Brenda Temperoni; Carla Derisio; María Sofía Dutto; Anabela Berasategui; Irene Ruth Schloss; Rodrigo Javier Gonçalves (Data)
The present dataset served to evaluate the plankton community composition and abundance in Nuevo Gulf (42°42′ S, 64°30′ W), a World Heritage Site in Argentinian Patagonia and part of the Valdés Biosphere Reserve. It reports zooplankton abundance (>300 µm) and phytoplankton concentration (10–200 μm) during the spring and summer seasons from 2019 to 2021. Special attention was given to the taxonomic classification of zooplankton, leading to the first identification of jellyfish species within the Gulf and the detection of an unreported copepod for the area (Drepanopus forcipatus). Samples were collected at two depths—a surface and a deeper layer—to assess vertical distribution patterns of plankton communities and explore potential environmental drivers influencing their variability. This dataset provides a valuable baseline for future studies analyzing temporal variations in the Gulf’s plankton communities. Moreover, it encourages the local scientific community to contribute data and promote open access to marine biodiversity records in the region.